Secondary infection in immuno-competent children with dengue: Case series - Pandey, Mukul; Mittal, Hema (Indian Journal of Child Health, 2014)
The occurrence of bacterial superinfection, or coinfection, in patients with dengue, has been previously reported, but the available information comes from anecdotic reports. We report clinical and pathological data of immunocompetent children diagnosed with dengue and had evidence of concurrent bacterial infections.